Photo-electrocatalytic hydrogen generation at dye-sensitised electrodes functionalised with a heterogeneous metal catalyst. (20th November 2016) - Hoogeveen, Dijon A.; Fournier, Maxime; Bonke, Shannon A.; Fang, Xi-Ya; Mozer, Attila J.; Mishra, Amaresh; Bäuerle, Peter; Simonov, Alexandr N.; Spiccia, Leone
Abstract: Dye-sensitised photocathodes promoting hydrogen evolution are usually coupled to a catalyst to improve the reaction rate. Herein, we report on the first successful integration of a heterogeneous metal particulate catalyst, viz., Pt aggregates electrodeposited from acidic solutions on the surface of a NiO-based photocathode sensitised with a p -type perylenemonoimid-sexithiophene-triphenylamine dye (PMI-6T-TPA). The platinised dye-NiO electrodes generate photocurrent density of ca −0.03 mA cm −2 (geom.) with 100% faradaic efficiency for the H2 evolution at 0.059 V vs. reversible hydrogen electrode under 1 sun visible light irradiation (AM1.5G, 100 mW cm −2, λ > 400 nm) for more than 10 hours in 0.1 M H2 SO4 (aq.). The Pt-free dye-NiO and dye-free Pt-modified NiO cathodes show no photo-electrocatalytic hydrogen evolution under these conditions. The performance of these Pt-modified PMI-6T-TPA-based photoelectrodes compares well to that of previously reported dye-sensitised photocathodes for H2 evolution.